2017
DOI: 10.1053/j.gastro.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones: Bad Company for the Steatotic Liver

Abstract: is an Advisory board member for Gilead Sciences, Abbvie, Bristol-Myers Squibb (BMS), and Merck; a speaker for Gilead Sciences, Abbvie, Merck, BMS, Roche Diagnostics; and receives research/grant support (to institution) from Gilead, Abbvie. J. Howell discloses no conflicts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…1M ). These data suggested that the oral administration of L. reuteri and L. plantarum could ameliorate the histological damage in the gallbladder and liver and improve the hepatic steatosis and liver lipid metabolism, which is associated with reduction of CGS formation ( 28 , 29 ).…”
Section: Resultsmentioning
confidence: 88%
“…1M ). These data suggested that the oral administration of L. reuteri and L. plantarum could ameliorate the histological damage in the gallbladder and liver and improve the hepatic steatosis and liver lipid metabolism, which is associated with reduction of CGS formation ( 28 , 29 ).…”
Section: Resultsmentioning
confidence: 88%
“…1H). These data suggested that the oral administration of LR and LP can ameliorate hepatic steatosis, which is associated with cholesterol gallstones [24]. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) were similarly reduced in the LR and LP treated groups (Fig.…”
Section: Lr and Lp Treatments Reduced Ld-induced Gallstones And Metabmentioning
confidence: 72%
“…Previously, abdominal visceral fat accumulation[ 5 - 7 ] and excessive heme iron consumption[ 8 ] were found to be related to a higher risk of gallstone disease. Liver fat accumulation associated with increased body cholesterol synthesis and hypersecretion of biliary cholesterol may also be related to cholelithiasis development[ 7 ], and nonalcoholic fatty liver disease (NAFLD) is an independent risk factor for cholelithiasis development[ 9 - 11 ] as well as gallstone-related diseases with an odds ratio (OR) of 3.6[ 12 ].…”
Section: Introductionmentioning
confidence: 99%